Cytokine balance as a diagnostic marker of inflammation in experimental purulent lesions of soft tissues - A. S. Solovyeva; G. G. Melkonyan; A. N. Koval; N. V. Tashkinov; N. Yu. Rukina; O. A. Shokur; Yu. A. Sapozhnikov (Медицинская иммунология, 2023)
Inflammatory process is at the heart of artificial (artificial) purulent-inflammatory diseases of soft tissues (APDST), which may lead to the development of phlegmon and abscesses at the site of invasion within a three-day period. The study of the cytokine status of rats with APDST allows us to evaluate the dynamics of inflammation markers and assess the peculiarities of the pathological course in artificial model of inflammation. The experiment was carried out on 126 white Wistar rats divided into 3 groups: (1) the main group (n = 57), where the laboratory model of APDST was used; (2) a comparison group (n = 58), in which the rats were injected with a mixture of opportunistic bacterial strains isolated from pure cultures of human oral fluid, i.e., S. epidermidis, S. mitis, S. salivarius at the titer of 9lg (CFU) per 1 ml injected together with a mixture of 2.5% hydrocortisone acetate emulsion (20 mg per 100 g of animal body weight), and dexamethasone solution at the dose of 0.5 mg; (3) control group (n = 11), where the animals were injected with 0.9% sodium chloride solution in a volume of 0.3 ml, together with a mixture of 2.5% hydrocortisone acetate emulsion at the rate of 20 mg per 100 g of body weight, and dexamethasone solution at the dose of 0.5 mg. Blood cells were studied using the Mindray DC-2800 Vet Auto Hematology Analyzer automated rat blood test system. The dynamics of pro-inflammatory cytokines: tumor necrosis factor (TNF), interleukin-1β (IL-1β), interleukin-6 (IL-6), antiinflammatory cytokines: interleukin-4 (IL-4), interleukin-10 (IL-10) was assessed by enzyme immunoassay. To predict the course of inflammation towards complications, or resolution of the inflammatory process, the ratio of pro-inflammatory to anti-inflammatory cytokines was used, with normal ratio considered an estimated average of the cytokine ratio for the control group. When analyzing results of this experimental study, the nature of cellular inflammatory response was assessed in dynamics, and its relationship with inflammation markers was determined. All animals of the main group developed soft tissue phlegmon within 3 to 7 days from the beginning of the experiment, and their mortality rate was 100%. In comparison group, the abscesses developed in 82.8% of cases on the day 12 to 15 from the start of the experiment, without any deaths observed. The ratio of pro- and anti-inflammatory cytokines in the main group increased 8-fold already by the end of the 1st day, the comparison group was characterized by the absence of significant differences from the control group. The highest levels of pro-inflammatory cytokines were recorded in the main experimental group on the days 12 to 15.